2016
DOI: 10.1007/s00726-016-2234-z
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrases are producers of S-nitrosothiols from inorganic nitrite and modulators of soluble guanylyl cyclase in human platelets

Abstract: Nitric oxide (NO), S-nitrosoglutathione (GSNO) and S-nitrosocysteine are highly potent signaling molecules, acting both by cGMP-dependent and cGMP-independent mechanisms. The NO metabolite nitrite (NO2 (-)) is a major NO reservoir. Hemoglobin, xanthine oxidoreductase and carbonic anhydrase (CA) have been reported to reduce/convert nitrite to NO. We evaluated the role and the physiological importance of CA for an extra-platelet CA/nitrite/NO/cGMP pathway in human platelets. Authentic NO was analyzed by an NO-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 38 publications
2
32
1
Order By: Relevance
“…Previously, CAII inhibitors, such as dorzolamide, were shown to paradoxically increase NO production from nitrite and bovine CAII using a NO‐specific electrode by Aamand et al (), although no clear mechanism for this was established. However, we found no effect of dorzolamide on NO‐production using NO chemiluminescence (data not included), in line with recent other reports (Andring et al, ; Hanff et al, ). The mechanism of CAII inhibition by dorzolamide has been well characterized, and structural data illustrate that dorzolamide and related inhibitors bind directly to the zinc in the active site of CAII (Pinard, Boone, Rife, Supuran, & McKenna, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previously, CAII inhibitors, such as dorzolamide, were shown to paradoxically increase NO production from nitrite and bovine CAII using a NO‐specific electrode by Aamand et al (), although no clear mechanism for this was established. However, we found no effect of dorzolamide on NO‐production using NO chemiluminescence (data not included), in line with recent other reports (Andring et al, ; Hanff et al, ). The mechanism of CAII inhibition by dorzolamide has been well characterized, and structural data illustrate that dorzolamide and related inhibitors bind directly to the zinc in the active site of CAII (Pinard, Boone, Rife, Supuran, & McKenna, ).…”
Section: Discussionsupporting
confidence: 93%
“…Despite the fact that CAII is expressed abundantly in red blood cells, we found that CAII KO red blood cells exhibited similar nitrite‐dependent platelet inhibition compared with wild‐type red blood cells (Figure ). Recently, Hanff et al () reported that nitrite and CAII can generate S‐nitrosothiols (RSNOs) in the presence of cysteine, but we did not observe in vivo or in vitro vasodilation with CAII KO (Figures and ). While RSNOs are potent vasodilators, our observation suggests that this chemistry is not occurring in vivo.…”
Section: Discussioncontrasting
confidence: 79%
“…The CA I isoform is available in cerebral and retinal illness, and we pursued the supposition that proteins of the CA I isoform could demonstrate treatment purposes for inhibiting CA I‐induced vascular permeance . The HCA I isoform is significantly expressed in the human body, and it is available in great concentrations in the gastrointestinal tract and blood .…”
Section: Discussionmentioning
confidence: 99%
“…4.2.1.1), as isoforms I and II, are extremely available in the gastrointestinal tract and in red blood cells of vertebrates, arriving at concentrations as high as 0.2 mM and having a significant role in blood pH homeostasis as well as in carrying carbon dioxide (CO 2 ) to the lungs. [ Both of these cytosolic isoenzymes are the predominant ones among the 16 CAs recorded throughout history in the tissues of vertebrates/different cells . Twelve of them are described by a common Zn 2+ ion at the active site, while they differ in tissue and organ expression, molecular features, catalytic activity cellular localization, and how they respond to various groups of inhibitors …”
Section: Introductionmentioning
confidence: 99%
“…In this test, variations in absorbance were obtained during 3 min at 30°C. p ‐Nitrophenyl acetate (NPA) was used as a substrate and transformed by both isoforms to p ‐nitrophenolate ion . Sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS–PAGE) was examined for registration of both isoforms purity .…”
Section: Methodsmentioning
confidence: 99%